The Effect of Supervision and Work Climate on Organizational Commitment with Work Discipline as an Intervening Variable at The Bank Indonesia Representative Office in North Sumatra Province - M. Ilham Hidayat; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
In this era of globalization, quality human resources are needed and become capital for the business world to continue to grow and prosper. To achieve results in accordance with expectations, human resource development must be pursued as much as possible. Supervision is essentially a function inherent in a leader or top management in any organization, along with other basic management functions such as planning and execution. This study was conducted with the aim of examining the Influence of Supervision and Work Climate on Organizational Commitment with Work Discipline as an Intervening Variable in the Bank Indonesia Representative Office in North Sumatra Province. The results of this study are as follows: Work Discipline has a positive and insignificant effect on Organizational Commitment with the original sample of 0.126 and p values of 0.289. Work Climate had a positive and significant effect on Work Discipline with the original sample value of 0.264 and p values of 0.012. Work Climate had a positive and significant effect on Organizational Commitment with the original sample value of 0.525 and p values of 0.004. Supervision had a positive and significant effect on work discipline with an original sample value of 0.639 and p values of 0.000. Supervision had a positive and insignificant effect on Organizational Commitment with the original sample value of 0.131 and p values of 0.251. Work Climate had a positive and insignificant effect on Organizational Commitment through Work Discipline with the original sample value of 0.033 and p values of 0.312. Supervision has a positive and insignificant effect on Organizational Commitment through Work Discipline with the original sample value of 0.081 and p values of 0.293.